Histopathological Aspects Described in Patients with Hepatic Hydatidosis - Mihăilă Daniela E.; Niţu M.C; Potecă T.D (Sciendo, 2016)
Introduction. Hydatidosis is a parasitic disease with tumour-like development of a cystic mass. This has specific endemic areas, Romania being amongst them. Our hospital has national addressability and the collaboration between the Departments of Parasitology, General Surgery and Pathology ensures optimal multidisciplinary approach to cases of therapeutic and diagnostic standpoint. The study aims to test the hypothesis that the gallbladder is a hydatid reservoir, to identify signs of biliary fistulas in the pericyst and liver parenchyma; to identify inflammation elements in the pericyst and the gallbladder.